Community evolution increases plant productivity at low diversity. (16th November 2017) - van Moorsel, Sofia J.; Hahl, Terhi; Wagg, Cameron; De Deyn, Gerlinde B.; Flynn, Dan F. B.; Zuppinger‐Dingley, Debra; Schmid, Bernhard
Abstract: Species extinctions from local communities negatively affect ecosystem functioning. Ecological mechanisms underlying these impacts are well studied, but the role of evolutionary processes is rarely assessed. Using a long‐term field experiment, we tested whether natural selection in plant communities increased biodiversity effects on productivity. We re‐assembled communities with 8‐year co‐selection history adjacent to communities with identical species composition but no history of co‐selection ('naïve communities'). Monocultures, and in particular mixtures of two to four co‐selected species, were more productive than their corresponding naïve communities over 4 years in soils with or without co‐selected microbial communities. At the highest diversity level of eight plant species, no such differences were observed. Our findings suggest that plant community evolution can lead to rapid increases in ecosystem functioning at low diversity but may take longer at high diversity. This effect was not modified by treatments simulating co‐evolutionary processes between plants and soil organisms.